One-Stage Ear Reconstruction After Avulsion Injury, Using the Amputated Cartilage and a Retroauricular Transposition Flap - Manoli, Theodora (Open Science Company, LLC, 2010)
Introduction: Auricular reattachment or reconstruction after traumatic ear loss remains a challenge for the plastic reconstructive surgeon. Because of the diverse accident mechanisms, no standard algorithms exist and several modalities have been proposed in the literature. Methods: A case of an innovative ear reconstruction of a partially avulsed ear is presented. The amputated cartilage was reattached after being deepithelized from the anterior skin. A transauricular-retroauricular random pattern flap was then harvested and used for anterior skin coverage. Results: The described technique provided a nice final result without the need of any further operations. Conclusion: In general, a microsurgical replantation should be applied when the circumstances allow. In other cases, especially in partial upper-ear amputations with severe skin contusions, the described technique should be considered as a safe, single-step approach with good final results.